IMPROVING STUDENTS VOCABULARY MASTERY BY USING TEXT TWIST GAME AT SMAN 8 SELAYAR - Nuraeni Nuraeni; Haryanto Atmowardoyo; Ahmad Talib (Universitas Negeri Makassar, 2022)
This research is about the use of the Text Twist game to teach vocabulary to the tenth-grade students of SMAN 8 Selayar. The objective of this research is to find out whether or not the use of Text Twist games improves vocabulary mastery of the tenth-grade students of SMAN 8 Selayar. The research design used in this research is a pre-experimental with one group pretest-posttest design. The sample was from class X MIA 1 which consists of 25 students and a cluster random sampling technique was used for the data selection. In obtaining the data, the researchers used the test as an instrument. The researchers analyzed the data quantitatively by using inferential statistics SPSS 26. The results of the data analysis showed that by using the Text Twist game, students' vocabulary mastery improved. It can be proven by the acquisition of significance value (2- tailed) which was 0.000 (0.000 < 0.05). It means H0 is rejected and H1 is accepted. So, it can be concluded that the use of the Text Twist Game improves students' vocabulary among the tenth-grade students of SMAN 8 Selayar.